Association of exposure to ambient Ozone with sleep quality in pregnant women - Yun Huang; Jianing Wang; Yudiyang Ma; Hong Jin; Kun Sun; Yaohua Tian; Jun Zhang (BMC Pregnancy and Childbirth)
Abstract No study has investigated the associations between ozone (O3) exposure and sleep among pregnant women. This study examined the association of O3 exposure with sleep quality in Chinese pregnant women. We analyzed data in 7,581 pregnant women. Data on O3 exposure during different periods was obtained from ChinaHighO3 dataset. Maternal sleep quality was evaluated at enrollment using the Pittsburgh Sleep Quality Index (PSQI) questionnaire. Multivariable linear regression models were applied to explore relationships between the global score of PSQI and O3 exposure. Logistic regression models were applied to investigate associations between O3 exposure and the risk of poor sleep quality and sleep disturbances defined by different PSQI components. After adjusting confounders, PSQI score [and 95% confidence intervals (95%CIs)] increased by 0.24 (0.05, 0.43), 0.44 (0.23, 0.65), and 0.20 (0.12, 0.28), associated with per interquartile range increase in O3 exposure during 3, 6, and 12 months before pregnancy, respectively. The respective odds ratios (ORs) and 95% CIs of poor sleep quality were 1.11 (0.97, 1.28), 1.27 (1.08, 1.48), and 1.12 (1.06, 1.19). O3 exposures during different preconceptional exposure windows were associated with an increased PSQI score and a higher prevalence of poor sleep quality, longer sleep latency, and lower sleep efficiency.